An Analysis of The Promotion Mix of Zoya Fashion and Hijab - Hadi, Belani Asmara (Proceedings International Conference on Education Innovation and Social Science, 2024)
Marketing is a plan that enables a company to optimally utilize its resources to achieve its objectives. The success of marketing is largely determined by how promotions are conducted. This study is based on the dynamics of the promotion mix utilization at Zoya Fashion and Hijab, which experienced a decline in product sales during the Covid-19 pandemic from 2019 to 2021, but has since stabilized. The purpose of this research is to analyze the promotion mix of Zoya Fashion and Hijab and to provide approaches to enhance their promotion mix. This study employs a qualitative method with a descriptive approach, collecting data through interviews, observations, and documentation. Informants in this research include Zoya Fashion and Hijab management board, store supervisor and customers. The study applies the promotion mix theory, revealing that advertising, personal selling, sales promotion, public relations and publicity, as well as direct marketing, have been continuously and optimally implemented by Zoya Fashion and Hijab.